Formulation and evaluation of ranolazine extended release tablets: Influence of polymers - TEGK, Murthy; Mukkala, Bala Vishnu Priya; Babu VV, Suresh (Asian Journal of Pharmaceutics (AJP), 2014)
An extended release tablet provides prolonged periods of drug in plasma levels thereby reduce dosing frequency,improve patient compliance and reduce the dose-related side effects. Ranolazine is indicated for the chronic treatment of angina in patients who have not achieved an adequate response with other anti-anginal agents. The present investigationwas undertaken to design extended release tablets of Ranolazine employing hypromellose phthalate grade HP-55, ethocel standard 7FP premium ethyl cellulose, Surelease E-7-19040, Klucel HF pharm and Natrosol Type 250 HHX as matrix forming agents using wet granulation method. Formulated tablets were evaluated for uniformity of weight, assay, water content, in vitro drug release studies and stability studies.The drug release followed first order kinetics with both erosion and diffusion as the release mechanism. It is concluded that the desired drug release pattern can be obtained by using natrosol type 250 HHX compared to other polymers. The similarity factor (f2) was calculated to select best formulation by comparing in vitro dissolution data of the commercial formulation RanexaÂ®. The formulated tablets fulfilled the compendia requirements. The formulated Ranolazine Extended release tablets were found to be stable.